An Alternative Exposition of the Factor Price Equalization Theorem - Smith, William Paul (Quarterly Journal of Economics, 1961)
Journal Article An Alternative Exposition of the Factor Price Equalization Theorem Get access William Paul Smith William Paul Smith Michigan State University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 75, Issue 3, August 1961, Pages 506–507, https://doi.org/10.2307/1885140 Published: 01 August 1961